Al2O3-YAG eutectic ceramic prepared by laser additive manufacturing with water-cooled substrate. Issue 3 (15th February 2019) - Wu, Dongjiang; Liu, Hanchao; Lu, Fan; Ma, Guangyi; Yan, Shuai; Niu, Fangyong; Guo, Dongming
Abstract: The Al2 O3 -YAG eutectic ceramic was prepared by laser additive manufacturing on the substrate without water cooling and with water cooling, respectively. Furthermore, the temperature distribution, microstructure, phase structure, microhardness and fracture toughness of the deposited ceramic were investigated. The results indicated that the peak temperature on the water-cooled substrate decreased, and the cooling rate increased to 300 times compared to that without water cooling. Compared to the microstructure in the sample without water cooling, the microstructure in the sample with water cooling changed from the network structure to colony and dendrite structure, and the average eutectic spacing was reduced by 78.1%, and the plane (21 3 ¯ 0) diffraction intensity of Al2 O3 was enhanced, which was beneficial to reduce the dislocation accumulation. Also, under the water-cooled condition, the microhardness of Al2 O3 -YAG increased about 10.6%, to 21.50 ± 2.70 GPa, and the fracture toughness increased 8.5%, to 5.86 ± 1.11 MPa m 1/2, compared to those without water cooling.